Aspects of one-carbon metabolism in micro-organisms - Large, P (1962)
Pseudomonas AM1, pink bacterium which can grow on the one-carbon compounds methanol, formate and methyl- amine as sole carbon and energy sources has been the principal object of study in the work described. The pathway of carbon incorporation during growth on formate has been studied by chromatographic examination of the non-volatile ethanol-solubie radioactive cell constituents in samples taken over a period of 2 minutes after administration of [14C]formate or [14C]bicarbonate to cells growing on non-radioactive formate. It was found that the primary product of [14C]formate fixation was serine, and that of [14C]bicarbonate fixation was malate. At later times phosphorylated compounds, other amino acids, and trehalose acquired radioactivity. It ie concluded that the assimilation of formate in P. AM1 does not follow an autotrophic pathway, in which 3-phosphoglyceric acid would be the principal early product. A pathway for synthesis of cell constituents operating during growth on formate has been proposed. This involves the conversion of the reduced C1 compound to methylenetetrahydrofolate, the fixation of this into serine by serine transhydroxyrnethylase, the conversion of the serine to phosphoenolpyruvate and carboxylation of the latter to C4-dicarboxylic acids. The operation of such a biosynthetic route necessitates the synthesis glycine from C1 units. It is suggested that this process could come about by a direct condensation of two C1 compounds, or by a cyclic series of reactions involving the formation of glycine from the C4 end-product. In an attempt to obtain further evidence for this hypothesis an investigation into the enzymes present in cell-free extracts of formate-grown P. AM1 has been made. It was found that all the enzymes are present for the conversion of formate and glycine to 3-phosphoglycerate. Extracts supplemented by the appropriate cofactors could bring about the conversion of [14C]formate to [14C]- glycerate and [14C]glycerate to 3-phospho[14C]glycerate. The specific activities of all the enzymes involved in these transformations were higher in cells grown on formate than in cells grown on succinate. This observation is taken as evidence that these enzymes do indeed play a special role in the growth of P. AM1 on C1 compounds. The specific activities of all the enzymes are of the correct order of magnitude to explain the overall observed rate of growth on formate. Glycine, serine and phosphoglyceric acid have been isolated from the ethanol-soluble fraction of cells grown for 1 min. on [14C]methanol, and degraded. Similar degradations have also been performed on glycine and serine derived from cells grown for 1 min. on [14C]- methanol but aerated with air containing 1% v/v carbon dioxide. The distribution of radioactivity indicates that the carboxyl groups of glycine and aerine are derived from carbon dioxide, that C-3 of serine is derived from a reduced C1 unit, and that C-2 of glycine and C-2 of serine are also derived from a reduced C1 unit, but less directly than C-3. Comparison of these patterns with those of malate derived from the same source indicated that serine could not have been formed from malate, but that malate could have been formed from serine. Cell-free extracts of methanol-grown P. AM1 contain an enzyme which on purification has been shown to be a phosphoenolpyruvate carboxylase, catalysing the irreversible formation of oxaloacetate and orthophosphate from phosphoenolpyruvate and bicarbonate. The properties of the enzyme have been investigated. The enzyme is specific for phosphoenolpyruvate (for which Km is 3.3 x 10-4M), inhibited by phosphate and ammonium ions, not stimulated by ADP or GDP, and activated specifically by Mg2+ ions. The pH optimum is 8.5. The enzyme has been assigned a key role in the formation of C4 compounds from C3 compounds. Attempts have been made, both in whole cells and in extracts to determine the origin of the glycine necessary for the above biosynthetic scheme. Studies on the metabolites formed from [2, 3-14C2]succinate after short- term incubation with whole cells of methanol-grown P. AM1 indicated that glycine could possibly be formed from C4 dicarboxylic acids by a pathway not involving C3 compounds or phosphates. It was not found possible, however, to demonstrate this in extracts. Experiments on the carboxylation of reduced C1 units in extracts were also unsuccessful. Experiments on the oxidation of methanol, formaldehyde and formate by washed suspensions and extracts of formate- and methanol-grown P. AM1 have been performed. Whole cells rapidly oxidised all three substrates. The only enzyme demonstrable in extracts with a specific activity of the correct order to explain the oxidation rate of whole cells was an NAD-linked formate dehydrogenase. Evidence against the participation of